Implementation of Land Revenue for The Construction of Toll Road from Pandaan to Malang - Wicaksono, Moch.Yuris; Rokhim, Abdul; Muhibbin, Moh.; Limsira, Patthara (International Journal of Business, Law, and Education, 2024)
The purpose of this study is to understand how landowners make payments for development according to Law No. 10. Law No. 2 of 2012 regarding the process of legal solution in case of land acquisition for public benefit development and right holders not accepting the decision and/or money amortization study. The research used in this article is legal research and the following points can be deduced: (1). Payments are made in accordance with Law No. 1. The "Public Development Research Report" No. 2 of 2012 states that the payment to the right holders during land acquisition is reasonable and fair. The compensation amount is calculated based on the base parcel, including land, aboveground and underground, buildings, factories, underground equipment and other damages. According to the analysis of the payment, payments can be made according to money, land transfer, relocation, equity capital and other agreements to be made by both parties. (2). In other words, the legal solution to payment problems is that in case of objection to the document and payment, the beneficiary can appeal to the regional court within 14 business days after signing the payment document. Additionally, the District Court has the authority to determine the form and/or compensation within 30 business days from receipt of the complaint. Those who object to the decision of the regional court may appeal to the Court of Cassation within 14 working days. In this case, the Court of Cassation must make a decision within 30 working days after receiving the application for decision